The p.A2215D thyroglobulin gene mutation leads to deficient synthesis and secretion of the mutated protein and congenital hypothyroidism with wide phenotype variation - Pardo, Viviane (2009)
Context: Thyroglobulin (TG) is a large glycoprotein and functions as a matrix for thyroid hormone synthesis. TG gene mutations give rise to goitrous congenital hypothyroidism (CH) with considerable phenotype variation. Objectives: The aim of the study was to report the genetic screening of 15 patients with CH due to TG gene mutations and to perform functional analysis of the p.A2215D mutation. Design: Clinical evaluation and DNA sequencing of the TG gene were performed in all patients. TG expression was analyzed in the goitrous tissue of one patient. Human cells were transfected with expression vectors containing mutated and wild-type human TG cDNA. Results: All patients had an absent rise of serum TG after stimulation with recombinant human TSH. Sequence analysis revealed three previously described mutations (p.A2215D, p.R277X, and g.IVS30+1G>T), and two novel mutations (p.Q2142X and g.IVS46-1G>A). Two known (g.IVS30+1G/p.A2215D and p.A2215D/p.R277X) and one novel (p.R277X/g.IVS46-1G>A) compound heterozygous constellations were also identified. Functional analysis indicated deficiency in TG synthesis, reduction of TG secretion, and retention of the mutant TG within the cell, leading to an endoplasmic reticulum storage disease, whereas small amounts of mutant TG were still secreted within the cell system. Conclusion: All studied patients were either homozygous or heterozygous for TG gene mutations. Two novel mutations have been detected, and we show that TG mutation p.A2215D promotes the retention of TG within the endoplasmic reticulum and reduces TG synthesis and secretion, causing mild hypothyroidism. In the presence of sufficient iodine supply, some patients with TG mutations are able to compensate the impaired hormonogenesis and generate thyroid hormone.